Implementation of Collaborative Governance on Village Fund Management in the Development of Umbul Tirah Tourism Village - Dianita, Jiva Diyah; Pravasanti, Yuwita Ariessa; Pratiwi, Desy Nur (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2025)
This research aims to determine the Collaborative Governance process for managing the Umbul Tirah Development and the factors that influence the success of the Collaborative Governance model which focuses on face-to-face dialogue, building trust, commitment to the process, mutual understanding, and collaboration results. The method used is qualitative with the support of data analysis techniques including data collection, data reduction, and data presentation, as well as conclusion. The results of the research show that the dialogue that existed in the construction of Umbul Tirah, both officially and unofficially, built a sense of mutual trust in each other so that the construction of Umbul Tirah resulted in benefits for the community. This is also based on a commitment to share understanding and knowledge about managing village funds for the development of Umbul Tirah.